Aplikasi Belajar Berbasis Digital dapat Meningkatkan Motivasi Belajar Mahasiswa - Bintang Narpati; Milda Handayani; Eri Bukhari (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
The purpose of this study is to measure how the role of digital based learning applications through smartphone facilities can influence learning motivation among students. The method used in this study was to use quantitative descriptive analysis involving 90 (ninety) students using random sampling techniques.This method of collecting data through a questionnaire method supported by the documentation method. Linear regression analysis is a technique used in analyzing this data. Based on the results of this study concluded: (1) There is a significant influence between digital-based learning applications on student learning motivation (2) There is a significant influence between smartphones on student learning motivation (3) There is a significant influence between digital based learning applications and smartphone against student learning motivation. Simultaneously with the presence of digital-based learning applications and through smartphone means can increase student learning motivation